Constructing and Validating a Performance Evaluation System for Highly Qualified Specialists: A Mixed-Methods Approach Based on Rough Set Theory and Analytic Hierarchy Process - Zhuang, Sumei (Academic Journal of Management Science and Engineering, 2026)
The effective performance evaluation of highly qualified specialists (HQS) remains a persistent challenge for Chinese enterprises transitioning to knowledge-intensive operations. Traditional evaluation systems, designed for routine work, fail to capture the multidimensional nature of HQS contributions, which encompass cognitive engagement, value congruence, and affective attachment. This study addresses this gap by developing and validating a comprehensive performance evaluation system specifically tailored to HQS. Using a mixed-methods design, the study first identified 22 candidate indicators through literature review and expert interviews. Rough set theory was then applied to reduce redundant indicators, yielding a parsimonious 17-indicator system organized across four dimensions: work engagement (5 indicators), organizational identification (4 indicators), value identification (4 indicators), and emotional belonging (4 indicators). Analytic Hierarchy Process (AHP) was subsequently employed to determine indicator weights, revealing that value identification (weight = 0.4564) and emotional belonging (weight = 0.2219) are the most influential criterion-level dimensions. At the indicator level, company culture (0.1896) and management systems (0.1336) emerged as the most heavily weighted individual measures. Confirmatory factor analysis (CFA) of survey data from 562 HQS in Chinese enterprises demonstrated good model fit (χ²/df = 2.462, GFI = 0.940, CFI = 0.939, RMSEA = 0.051), providing empirical validation of the proposed system. This study contributes a theoretically grounded, empirically validated, and practically operational evaluation system that enables Chinese enterprises to assess HQS performance more comprehensively and systematically.
Keywords: Performance Evaluation System; Highly Qualified Specialists; Rough Set Theory; Analytic Hierarchy Process; Confirmatory Factor Analysis; Chinese Enterprises